2014
DOI: 10.1039/c4dt01340a
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous liquid–liquid extraction of neodymium(iii) by choline hexafluoroacetylacetonate in the ionic liquid choline bis(trifluoromethylsulfonyl)imide

Abstract: The ionic liquid choline bis(trifluoromethylsulfonyl)imide, [Chol][Tf2N], was used for the extraction of neodymium(III), in combination with choline hexafluoroacetylacetonate, [Chol][hfac], as the extractant. The binary mixture of [Chol][Tf2N] and water shows temperature-dependent phase behavior, with an upper critical solution temperature of 72 °C. A novel extraction technique, homogeneous liquid-liquid extraction (HLLE), was applied to this solvent system. HLLE is based on the use of thermomorphic solvent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 82 publications
1
67
0
Order By: Relevance
“…From these results, it can be concluded that [Hbet][Tf 2 N] system is of more interest than the [Chol][Tf 2 N] system because the phases in the latter system are less pure and thus less interesting for solvent extraction systems. Moreover, choline is a very weak solvating ligand and extraction without the addition of an extra extractant is very difficult 16…”
Section: Resultsmentioning
confidence: 99%
“…From these results, it can be concluded that [Hbet][Tf 2 N] system is of more interest than the [Chol][Tf 2 N] system because the phases in the latter system are less pure and thus less interesting for solvent extraction systems. Moreover, choline is a very weak solvating ligand and extraction without the addition of an extra extractant is very difficult 16…”
Section: Resultsmentioning
confidence: 99%
“…[22] With regard to thermoresponsive IL-waters ystems, UCST-type systemsa re more popular as they can be utilised as extraction and separation solvents, which further broadens their applicationsi nc atalysis. [34][35][36] However,o nly few UCST-type IL-water systems are reported so far. [34][35][36][37] The most important one is the binary mixture of imidazolium-based ILs ([C n mim]BF 4 , n = 4, 6,8) and water,w hich shows tuneable UCST-type transitions depending on the length of the alkyl chain and also on the hydrophobicity of the anions.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] However,o nly few UCST-type IL-water systems are reported so far. [34][35][36][37] The most important one is the binary mixture of imidazolium-based ILs ([C n mim]BF 4 , n = 4, 6,8) and water,w hich shows tuneable UCST-type transitions depending on the length of the alkyl chain and also on the hydrophobicity of the anions. [37] The reportso fb oth UCST-and LCST-type transitions of [P 4,4,4,4 ]-type ILs with fumarate and maleatei ons, respectively,f urthere nriched this area.…”
Section: Introductionmentioning
confidence: 99%
“…This system showed that effective extraction of trivalent rare-earth, indium, gallium, neodymium ions18, and uranyl species33 can be achieved by homogeneous extraction without additional any extractant. Homogeneous liquid–liquid extraction of neodymium(III) has also been achieved using choline hexafluoroacetylacetonate in the ionic liquid choline bis(trifluoromethylsulfonyl) imide34. Recently, Dupont et al .…”
mentioning
confidence: 99%